Effect-for-cause inferencing in the evaluation of loudness among Toba Batak people - Tobing, Andrew P.L.; Panggabean, Himpun; Sinar, Tengku Silvana (Sociolinguistic Studies, 2017)
The paper presents evidence for an effect-for-cause inferencing process underlying the general style of using loud speech voice among Toba Batak speakers (Indonesia). A subjective reaction test was conducted to find out their perception towards the use of loud voice in three relational settings having different combinations of bipolarity: 1) vertical social distance and horizontal social distance; 2) vertical social distance only; and 3) horizontal social distance only. The results showed that in contexts where horizontal social distance remains, the absence of vertical distance significantly weakens the perception of impoliteness and unacceptability towards the use of loud voice. This indicates that Toba Bataks assume a pseudo social proximity when they are speaking to people with whom they have no horizontal social closeness. This method of inferencing is consistent with an effect-for-cause relational structure, being metonymic in nature.